Hiding Information Using Circular Distribuition - Ahmed Ali, M.Sc.Rajaa; Khamees Mustafa, M.Sc.Muntadher; A. Alani, Ali (مجلة كلية التربية, 2020)
The Internet as a whole does not use secure links, thus information in transit may be vulnerable to interception as well. The important of reducing a chance of the information being detected during the transmission is being an issue now days. Therefore, different methods have been proposed so far for hiding information in different cover media. The carrier medium can be image, audio or video. Of the different carrier media, image is best chosen as the carrier due to its frequency on the internet. This paper proposes technique to hidden data in another medium. This technique hides an encoded audio message in the pixels of the carrier image using circular distribution algorithm. To measure the qualities of the cover file (stego image) after hides process used Peak Signal–to-Noise Ratio (PSNR). Only minor changes in the contents of the image file occur, which are indiscernible to human eyes.